P223 Update of the british occupational health foundation (bohrf) evidence-based guidelines on the prevention and management of occupational asthma. (15th November 2017) - De Matteis, S; Feary, J; Macfarlane, J; Romano-Woodward, D; Szram, J; Walters, G; Wiggans, R; Cullinan, P
Abstract : Introduction and Objectives: Occupational asthma (OA) can be prevented by eliminating or at least minimising exposures to the causal agents at work. However, the rapid development of industrial technologies constantly introduces new potential asthmagens at work and therefore up-to-date knowledge of these changes is pivotal to diagnose and prevent new OA cases. The current evidence-based guidance on the prevention and management of OA was commissioned by the British Occupational Health Foundation (BOHRF) in 2010. 1 Our aim was to update these guidelines to help stakeholders reducing the incidence of OA by improved prevention, and the severity of individual cases of disease by earlier identification and better management. Methods: We conducted a literature systematic review according to state-of-the-art methods via search of two electronic database (Embase and Medline), using the Ovid interface, from January 2009 to November 2016. Both MeSH and free-text terms were used for combinations of 'work' and 'asthma'. The retrieved references were managed using EndNote software and evaluated blindly by paired reviewers. Critical appraisal of the included articles was performed using the GRADE (Grading of Recommendations, Assessment, Development and Evaluations) scoring system to link evidence-quality evaluations to clinical recommendations. Results: From the 2424 references retrieved, 133 met the inclusion criteria (see attached PRISMA flow-chart diagram). Briefly, in terms of occupations, many previously identified were confirmed, such as bakers, and painters, but new ones emerged such as cleaners, suggesting also underlying irritative-mediated causal mechanisms. Not substantial changes in the diagnosis of OA emerged, but new potential frameworks for better management and health surveillance of OA arose. Conclusions: Exposure to respiratory hazards at work is still an important cause of asthma worldwide and in the UK, with important costs for both the individual and the society. Updated evidence-based guidelines on the prevention and management of OA are key to guide healthcare workers' decision-making in their routine clinical practice. Reference: British Occupational Health Research Foundation. Occupational Asthma – Identification, Management and Prevention: Evidence Based Review and Guidelines 2010. Available at http://www.bohrf.org.uk/downloads/Occupational AsthmaEvidenceReview-Mar2010.pdf